Estandarización de la composición de un peletizado con un hongo entomopatógeno (2018)
In this work we seek to standardize the composition of a culture medium so that a selection of raw materials can be made based on the nutritional composition that can provide the entomopathogenic fungus Beauveria bassiana; In terms of carbohydrates, it is chosen: arracacha, cassava flour, rice and corn, in terms of vitamins and minerals the B complex and kaolin are chosen respectively. After the selection, a bioinsecticide can be experimentally developed in pill for the purpose of combating the plague that attacks the oak Quercus humboldti of the Botanical Garden of Bogotá, for this five experiments are carried out varying the carbohydrates and keeping the proportion of the vitamin and vitamin C constant. The mineral These experiments are sterilized and subsequently inoculated with 1 ml of the corresponding mycelium of the microorganism; to guarantee the growth and therefore the sporulation of the fungus was deposited in the incubator at a temperature of 26 ° C for an approximate time of 25 days. Once the estimated time has elapsed, the pellets to which the microbiological tests are made are used to evaluate the viability of the fungus in each culture medium, yielding favorable results at the third level, with a spore concentration of 2. , 38 * 1011 and a germination index of 88.28%.